2001
DOI: 10.1159/000056109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclooxygenase-2 Inhibitor (Celecoxib) on the Infarcted Heart in situ

Abstract: Several attempts have been made to replace aspirin with compounds without gastric toxicity; a cyclooxygenase-2 (COX-2) inhibitor, celecoxib, and a nitric oxide-aspirin, NCX-4016, have been developed for this purpose. This paper compares effects of celecoxib, NCX-4016 and aspirin on production of prostacyclin (PGI2) and thromboxane A2 (TXA2) and activation of the inducible form of nitric oxide synthase (iNOS) in infarcted heart in situ. Aspirin was most effective in reducing myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…These authors demonstrated that the relative risk of developing cardiovascular events was greater than with the nonselective COX inhibitor naproxen. These conclusions were confirmed by experimental evidence in infarcted heart muscle; here celecoxib (5 mg/kg) lowered the ratio of PGI 2 /thromboxane because of a diminished PGI 2 production [2,5]. In the present study, the average medullary values of the ratio PGI 2 /TXA 2 are lower for celecoxib than for aspirin (table 4), suggesting that, as in heart muscle, celecoxib tips the ratio PGI 2 /TXA 2 in favor of thromboxane.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…These authors demonstrated that the relative risk of developing cardiovascular events was greater than with the nonselective COX inhibitor naproxen. These conclusions were confirmed by experimental evidence in infarcted heart muscle; here celecoxib (5 mg/kg) lowered the ratio of PGI 2 /thromboxane because of a diminished PGI 2 production [2,5]. In the present study, the average medullary values of the ratio PGI 2 /TXA 2 are lower for celecoxib than for aspirin (table 4), suggesting that, as in heart muscle, celecoxib tips the ratio PGI 2 /TXA 2 in favor of thromboxane.…”
Section: Resultssupporting
confidence: 87%
“…On the other hand, COX-2 inhibitors may predispose to thrombotic diseases, including myocardial infarction, and cause damage to the kidney [2,4]. In both heart and kidney, COX-2 inhibitors cause a decline in PGI 2 concentrations and a fall in the ratio prostacyclin/thromboxane [5,6]. In the current report, we compared the effects of Lomnicka/Karouni/Sue/Wessel/Bing …”
Section: Introductionmentioning
confidence: 97%
“…25 The effect of aspirin and celecoxib was previously described in the infarcted heart in situ. 27 Similar to the kidney, in the heart, aspirin did not change myocardial iNOS production and celecoxib lowered myocardial PGI 2 production but did not interfere with the induction of iNOS. 11 In summary, we have shown that both selective and nonselective COX-2 inhibitors cause a significant decline in prostacyclin and thromboxane in the renal medulla, whereas expression of COX-2 and iNOS remains unchanged.…”
Section: Inos and Cox-2mentioning
confidence: 88%
“…Therefore, Sal-B, the major functional component of S. miltiorrhiza Bge may be able to mediate the cardiovascular risk of celecoxib. The mechanism of celecoxib increasing cardiovascular risk is not clear, but there is some evidence that celecoxib might lower the production of prostacyclin without affecting the synthesis of thromboxane A 2 , contribution to a prothrombotic state (42). Sal-B exerts cardiovascular prevention via making balance with prostacyclin and thromboxane A 2 (43).…”
Section: Discussionmentioning
confidence: 99%